Impact of intraoperative parathyroid hormone monitoring on the management of patients with primary hyperparathyroidism. (19th November 2018) - Shawky, Michael; Abdel Aziz, Tarek; Morley, Simon; Beale, Timothy; Bomanji, Jamshed; Soromani, Christine; Lam, Francis; Philips, Ian; Matias, Michelle; Honour, John; Smart, Jamie; Kurzawinski, Tom R.
Abstract: Background/Objective: Intraoperative parathyroid hormone (IOPTH) monitoring during surgery for primary hyperparathyroidism (PHPT) could improve cure rate and simplify current care pathways. This study assesses the performance of US, MIBI and IOPTH monitoring and their impact on outcomes and perioperative strategy. Design: This is a retrospective study of a prospectively maintained database of patients who underwent parathyroidectomy guided by preoperative US, MIBI and IOPTH monitoring. Test performance (sensitivity, specificity, PPV, NPV, accuracy) and IOPTH added value (percentage of patients in whom test contributed to achieving cure) were calculated. Results: A total of 617 patients (median age 59 years, 75% females), 603 (97.7%) of them cured, were included in analysis. Sensitivity of US was higher than MIBI (78.2% vs 70%, P < 0.05), but both were inferior to IOPTH (98.6%, P < 0.05). US and MIBI were more sensitive at detecting single gland disease (SGD) than multigland disease (MGD) (85% vs 55% and 77.5% vs 45.5%, respectively, P < 0.05), while IOPTH performed well in both situations (98.8% vs 96.7%, P > 0.05). In 41 patients with incorrect US predictions, MIBI gave correct result only in 12 (29.3%) cases, while IOPTH gave correct predictions in all but one patient (97.6%). Minimally invasive parathyroidectomy (MIP) was completed in 409 patients, with a similar completion rate regardless whether both or one scan was positive. IOPTH added value was significant in whole cohort (14%) and in subgroups of patients with concordant vs discordant scans, minimally invasive vs conventional surgery, and initial vs reoperative surgery. Conclusions: Intraoperative parathyroid hormone monitoring is more accurate at predicting cure than US and MIBI are at identifying abnormal glands in patients undergoing parathyroidectomy for PHPT and significantly contributes to cure rate in range of clinical scenarios. This implies that its routine use could facilitate successful surgery in patients with single positive imaging and increase number of MIPs while maintaining high cure rate.